Learning supercharged : digital age strategies and insights from the edtech frontier - Schrum, Lynne; Sumerfield, Sandi (International Society for Technology in Education, 2018)
This book looks at new ways to energize and engage students and how to employ the latest technologies in creative and innovative ways.